Peru‐Chile upwelling dynamics under climate change. Issue 2 (23rd February 2015) - Oerder, Véra; Colas, Francois; Echevin, Vincent; Codron, Francis; Tam, Jorge; Belmadani, Ali
Abstract: The consequences of global warming on the Peru‐Chile Current System (PCCS) ocean circulation are examined with a high‐resolution, eddy‐resolving regional oceanic model. We performed a dynamical downscaling of climate scenarios from the IPSL‐CM4 Coupled General Circulation Model (CGCM), corresponding to various levels of CO2 concentrations in the atmosphere. High‐resolution atmospheric forcing for the regional ocean model are obtained from the IPSL atmospheric model run on a stretched grid with increased horizontal resolution in the PCCS region. When comparing future scenarios to preindustrial (PI) conditions, the circulation along the Peru and Chile coasts is strongly modified by changes in surface winds and increased stratification caused by the regional warming. While the coastal poleward undercurrent is intensified, the surface equatorial coastal jet shoals and the nearshore mesoscale activity are reinforced. Reduction in alongshore wind stress and nearshore wind stress curl drive a year‐round reduction in upwelling intensity off Peru. Modifications in geostrophic circulation mitigate this upwelling decrease in late austral summer. The depth of the upwelling source waters becomes shallower in warmer conditions, which may have a major impact on the system's biological productivity. Key Points: Climate change impact on the nearshore circulation Modification in the upwelling intensity and its geostrophic compensation Modification in the upwelled water sources